PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN PT. PEGADAIAN (PERSERO) PEKANBARU - Nanda, Sulvia; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
AbstractThis study was conducted at PT. Pegadaian (Persero) Pekanbaru which is located on Tuanku Tambusai Ujung No.821, Pekanbaru City, Riau. This study aims to determine the effect of the Working Capital Turnover and Accounts Receivable Turnover on Profitability at the Pekanbaru PT. Pegadaian (Persero) during the 2014-2018 period. The type of data used is quantitative data and the source of data used is secondary data. This data collection technique is a documentation technique. Hypothesis testing uses a simple linear analysis method and multiple linear analysis with the results showing that the working capital turnover and Accounts Receivable Turnover has a positive and significant effect on profitability at the PT. Pegadaian (Persero) Pekanbaru. By calculating the coefficient of determination (R2) obtained value of R Square of 0.303. It showed that the Working Capital Turnover and Accounts Receivable Turnover has an effect of 30,3% on profitability at PT. Pegadaian (Persero) Pekanbaru, while the remaining 69,7% is influenced by other variables not determined in this study. The results of this study are strengthened by the results of hypothesis testing through the f-test which shows the significance of working capital turnover and accounts receivable turnover below 0.05, which means working capital turnover and accounts receivable turnover have a significant effect on profitability (NPM). *Keywords: Working Capital Turnover, Accounts Receivable Turnover, Profitability (NPM)